Evaluation of the Cardiovascular Effect of Propofol using Echocardiography in Dogs - Patil, Harshal R; Khandekar, Gajendra S; Tripathi, Santoshmani D; Chauhan, Shalaka A; Saini, Dishant; Sawant, Rutuja L (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The propofol is commonly used anaesthetic agent in veterinary practice. Propofol has advantage of smooth and rapid induction although  causes cardiovascular changes. This study was designed to evaluate cardiovascular changes after induction of anaesthesia with propofol  on 12 female Mongrel dogs brought for laparoscopic ovariohysterectomy. The animals were sedated with butorphanol, induced with  propofol and maintenance of anaesthesia was done with isoflurane. All dogs underwent a detailed systemic investigation including  echocardiographic examination. Heart rate, pulse rate and respiratory rate decreased significantly after induction of anaesthesia,  whereas echocardiographic parameters like ejection fraction and cardiac output decreased significantly by 9% and 33%, respectively.  The propofol reduced the cardiac output along with decrease in arterial pressure. All these cardiovascular changes were in physiological  limits and for transient period, the values of all parameters came to their normal level after recovery.
Keywords: Cardiovascular changes; Echocardiography,; Dog; Propofol.